Cervical impairments in subjects with migraine or tension type headache: an observational study - del Blanco Muñiz, Jose Ángel; Sánchez Sierra, Alberto; Ladriñán Maestro, Arturo; Ucero Lozano, Roberto; Sosa-Reina, María Dolores; Martín Vera, Daniel (Frontiers in Neurology, 2024)
Objective: The aim of this investigation was to compare the thickness of the deep local muscles in the neck region, as well as local and widespread sensitivity and functionality, between individuals with migraine, Tension-Type Headache (TTH), and healthy controls. Methods: An observational study was conducted in accordance with STROBE guidelines. The flexor longus colli and multifidus were measured using B-mode ultrasound imaging. The upper trapezius, masseter, temporalis, tibialis anterior, and median nerve all underwent bilateral pressure-pain threshold (PPT) assessments. Results: Ninety participants were enrolled in the study. All subjects were equally divided into TTH, migraine and control groups. The PPT values exhibited lower thresholds in patients with TTH than both migraine and healthy participants. In the temporal muscle on both sides, patients with TTH exhibited a significantly lower threshold (p<0.001) than both migraine and healthy participants. In multifidus muscle cross-sectional area (CSA), no statistically significant differences were found between migraine patients and healthy subjects, both in relaxation and contraction (right; p>0,05 and p>0,05; left: p>0,05 and p>0,05; However, patients with TTH exhibited a smaller CSA than both migraine patients and healthy controls in multifidus relaxed and contracted state (right: p<0.001 in both relaxed and contracted multifidus; left: p=0.001 and p<0.001, respectively). Similar results were obtained for the left longus colli muscle for patients with TTH and migraine compared with healthy subjects (p=0.001 and p<0.001, respectively, for muscle relaxation and p<0.001 for muscle contraction). In the right longus colli, TTH and migraine patients had a significantly smaller CSA during contraction than healthy subjects (p<0.001). In the craniocervical flexion test (CCFT), patients with TTH and migraine showed significantly lower values than healthy subjects. (p<0.001 in both comparisons). Conclusions: This study corroborates a lack of strength and smaller CSA in both clinical groups compared to controls. Therefore, strengthening programs may be addressed successfully for people with these pathological entities. According to PPTs and CSA lower values in patients with TTH compared to migraine and controls, manual therapy approaches to desensitize craniocervical soft tissues and exercise therapy to increase endurance of deep cervical muscles may become meaningful especially in subjects with TTH.